Recent Advancements in Aptamer-Based Surface Plasmon Resonance Biosensing Strategies - Chia‐Chen Chang (2021)
Surface plasmon resonance (SPR) can track molecular interactions in real time, and is a powerful as well as widely used biological and chemical sensing technique. Among the different SPR-based sensing applications, aptamer-based SPR biosensors have attracted significant attention because of their simplicity, feasibility, and low cost for target detection. Continuous developments in SPR aptasensing research have led to the emergence of abundant technical and design concepts. To understand the recent advances in SPR for biosensing, this paper reviews SPR-based research from the last seven years based on different sensing-type strategies and sub-directions. The characteristics of various SPR-based applications are introduced. We hope that this review will guide the development of SPR aptamer sensors for healthcare.